THE KNOWLEDGE OF RESPIRATORY INFECTIOUS DISEASE PREVENTION AMONG MEDICAL STUDENTS AT THE VIETNAM UNIVERSITY OF TRADITIONAL MEDICINE IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the knowledge of respiratory infection prevention among medical students at the Vietnam University of Traditional Medicine in 2025.Subjects and Methods: A descriptive cross-sectional study was conducted on 908 medical students from the 3rd to 6th academic years between May and October 2025 using a structured questionnaire. Data were collected and analyzed using Excel and SPSS version 22.0. Statistical significance was set at p 0.05).Conclusion: Medical students demonstrated fairly good to good levels of knowledge regarding respiratory infection prevention, which improved progressively with academic year.